ANALISIS KELAYAKAN DAN UJI KINERJA SHEET PRESS MACHINE DAUR ULANG SAMPAH PLASTIK - Muhammad Tama Tresno (2023)
Plastic waste has become one of the pressing environmental issues worldwide. To reduce the negative impact of plastic waste on the environment, plastic recycling has been widely adopted as a solution. In this thesis, a feasibility analysis and performance testing of a Sheet Press Machine on a micro-scale for plastic waste recycling are conducted. After the prototype is built, a series of performance tests are carried out. Performance testing includes measurements of bale density, machine capacity, efficiency, production speed, and the quality of the final product generated. The results of the performance tests are used to evaluate whether this machine meets the operational requirements necessary on a micro-scale. Furthermore, a feasibility analysis of the Sheet Press Machine is conducted in terms of technical and economic aspects. The results of the feasibility analysis and performance testing indicate that the micro-scale Sheet Press Machine has adequate capacity, good efficiency, sufficient production speed, and produces final products that meet the standards.